Effects of Curing Temperature on Electro-Optical Characteristics of a Polymer-Stabilized In-Plane-Switching Liquid Crystal Cell - Jae-Hyeon Woo; Tae-Hoon Choi; Byoung-Gyu Jeon; Tae-Hoon Yoon (Crystals, 2017)
We investigated the electro-optic characteristics of a polymer-stabilized, in-plane-switching (IPS) liquid crystal cell as the UV curing temperature was varied. We found that the response time of an IPS cell could be reduced through low-temperature UV curing of a low concentration of polymer material. We also found that fast switching could be achieved at a low operating voltage and with little light leakage in the dark state. Low-temperature curing of the polymer structure could greatly reduce the average distance between polymer bundles even at low polymer concentrations. Therefore, the decrease in transmittance of a polymer-stabilized IPS cell could be minimized by increasing the cell gap without sacrificing the response time because of the sufficiently high anchoring strength of the polymer structure obtained through low-temperature UV curing.